2021
DOI: 10.1177/1609406921993276
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evidence Synthesis: Where Are We at?

Abstract: Qualitative evidence syntheses (QES) have increased in prominence and profile over the last decade as a discrete set of methodologies to undertake systematic reviews of primary qualitative research in health and social care and in education. The findings from a qualitative evidence synthesis can enable a richer interpretation of a particular phenomenon, set of circumstances, or experiences than single primary qualitative research studies can achieve. Qualitative evidence synthesis methods were developed in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
155
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 57 publications
0
155
0
4
Order By: Relevance
“…This method combines approaches from both meta-ethnography and grounded theory and was originally developed to guide review of intervention needs, appropriateness, and effectiveness [ 26 , 28 ]. The approach of thematic synthesis is based on the method of thematic analysis used in primary qualitative research, however thematic synthesis enables new insights, interpretations and theories to be developed that has not been seen in the primary studies [ 29 ]. This meta-synthesis was prospectively registered with the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42020180051).…”
Section: Methodsmentioning
confidence: 99%
“…This method combines approaches from both meta-ethnography and grounded theory and was originally developed to guide review of intervention needs, appropriateness, and effectiveness [ 26 , 28 ]. The approach of thematic synthesis is based on the method of thematic analysis used in primary qualitative research, however thematic synthesis enables new insights, interpretations and theories to be developed that has not been seen in the primary studies [ 29 ]. This meta-synthesis was prospectively registered with the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42020180051).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research can provide an understanding of women's perspectives and lived experiences that cannot be captured using quantitative methods alone (Braun & Clarke, 2019). Reviewing and thematically synthesising this literature allows for the development of a richer interpretation and conceptual understanding that goes beyond the findings of individual studies, producing novel findings that are greater than the sum of its parts (Barnett-Page & Thomas, 2009;Evans & Pearson, 2001;Flemming & Noyes, 2021). A scoping review of the literature revealed a plethora of qualitative research, confirming our supposition that a qualitative review would be the most appropriate method to address the research question.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative evidence synthesis (QES) is a recognised method of integrating primary qualitative research findings in health and social care. 38 The methods of this QES are reported using the ENTREQ framework (online supplemental file 1). The research question and final search terms were ratified by a consensus panel of key stakeholders drawn from UK ambulance services and user advisory group of ESWs.…”
Section: Methodsmentioning
confidence: 99%